(untitled) (Research, Society and Development, 2024)
Type 2 diabetes mellitus (DM) is a chronic disease that often occurs alongside hypertension. Hypertension itself is a risk factor for vascular complications related to type 2 DM which will reduce the patient’s quality of life in the long term. This study aims to determine the characteristics of hypertension in type 2 DM patients. The research design was descriptive observational study using a total sampling technique by taking secondary data from medical record. The research sample was type 2 DM patients at the Internal Medicine Outpatient Clinic Prof. Dr. I. G. N. G. Ngoerah General Hospital in 2022 who meets the inclusion and exclusion criteria. Data analysis using Microsoft Excel and SPSS programs. Of the total 154 samples, hypertension in type 2 DM was mostly found in the 50-59 year age group (43.5%), male gender (62.3%) with duration of type 2 DM in the category <10 years (84.4%), normal total cholesterol levels (67.5%), abnormal LDL cholesterol levels (67.5%), normal triglyceride levels (59.1%), abnormal HDL cholesterol levels (63%) and normal e-LFG levels (51.9%). Further analysis is needed to determine the relationship between research variables and treatment history for dyslipidemia and kidney disease.